Political Tension and Stock Markets in the Arabian Peninsula - Alanoud Al-Maadid; Guglielmo Maria Caporale; Fabio Spagnolo; Nicola Spagnolo (Center for Economic Studies and ifo Institute (CESifo), 2018)
This note investigates the effects of the recent political tensions in the Arabian peninsula on the linkages between the stock markets of the leading GCC countries by estimating a VAR-GARCH (1,1) model at a weekly frequency. The results indicate that the June 2017 crisis lowered stock market returns and generally led to greater volatility spillovers within the region. This evidence supports the need for further financial integration and suggests fewer portfolio diversification opportunities for investors in the GCC region.
Keywords: C32; F36; G15; 330; GCC; multivariate GARCH; political tension